Adherence to stand-by emergency treatment and mosquito protection measures in short-term travellers to moderate malaria risk areas - Daniel Julien Franken; Vita Willemijn Jongen; Anna Rooyakkers; Martin Peter Grobusch; Jelte Elsinga; Margarita Boering; Maria Prins; Brigitte Antonia Geertruida Lucía van Cleef (New Microbes and New Infections)
Background: Malaria remains a threat to travellers to (sub)tropical regions. This study assessed adherence to malaria prevention measures among travellers to moderate-risk malaria areas, including the use of standby emergency treatment (SBET), healthcare-seeking behaviour during fever, and mosquito protection measures. Methods: We analysed data from adult travellers to moderate-risk malaria areas participating in a prospective study (2018–2023) at the Public Health Service of Amsterdam, the Netherlands. Participants maintained a daily diary during travel, recording questions about adherence to mosquito protection measures, symptoms, SBET use, and seeking medical help. In case of fever, participants were instructed to measure their temperature, use SBET if in a remote area, and seek medical help. We used Poisson regression to assess determinants for adherence to mosquito protection measures. Results: Of 686 recruited travellers, 405 (59 %) completed the diary. Of these travellers 44 % received a pre-travel SBET prescription, although presumably only a small fraction of them actually travelled remotely. None of the 25 travellers who reported fever used the prescribed SBET and five sought medical care. Thirty-five percent of participants used DEET and 5 % used a mosquito net on ≥75 % of the nights with malaria risk. Longer travel duration was associated with lower adherence to DEET use. Conclusions: Few travellers with fever used SBET or sought medical care, despite their pre-travel advice. To reduce costs and medication spillage, SBET should only be advised to travellers who travel to very remote regions where medical help is inaccessible. Further research should focus on the behavioural concepts underlying these choices.